2021
DOI: 10.5650/jos.ess20362
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of the Mixed Systems Containing 1,2-Dodecanediol against <i>Staphylococcus aureus</i> and <i>Staphylococcus epidermidis</i>

Abstract: S. epidermidis owing to its hydrophobic long alkyl chain.The antimicrobial behavior of 1,2-alkanediol in mixed systems with other components is unclear as only a single antimicrobial agent was added in these evaluation systems in previous study. However, various antimicrobial ingredients such as acids, salts, sebum and preservatives can coexist on the surface of the skin, if cosmetic and cleansing products containing 1,2-alkanediol are applied to keep the body clean and healthy 12 14 . These substances may aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(18 reference statements)
2
2
0
Order By: Relevance
“…[34] IPMP is typical of preservatives and bactericidal ingredients in cosmetics and is used in many oral care products. [35,36] These facts are consistent with the observation that HO tended to have higher antibacterial activity than RC.…”
Section: Discussionsupporting
confidence: 89%
“…[34] IPMP is typical of preservatives and bactericidal ingredients in cosmetics and is used in many oral care products. [35,36] These facts are consistent with the observation that HO tended to have higher antibacterial activity than RC.…”
Section: Discussionsupporting
confidence: 89%
“…IPMP is a typical preservative and bactericidal constituent in cosmetics and is used in commercial oral care products [41]. Phenolic compounds such as IPMP, phenoxyethanol, and ortho-phenylphenol are often thought to exhibit antimicrobial activity by damaging cell membranes and changing the membrane structure and function [42]. These facts are consistent with the observation that HO had higher antimicrobial activity than RC.…”
Section: Plos Onesupporting
confidence: 63%
“…Previously, Yamamoto et al evaluated the antibacterial activity of fatty acids and their metal salts against Staphylococcus aureus ( S. aureus ) and Staphylococcus epidermidis ( S. epidermidis ), and found that palmitoleic acid, its calcium salts and formulations containing them had selective antibacterial activity against S. aureus (Watanabe et al, 2019; Watanabe et al, 2021; Yamamoto et al, 2015, b; Yamamoto et al, 2017). The antibacterial activity of 1,2‐alkanediols was stronger if the alkyl chain length was longer (Okukawa et al, 2019; Okukawa et al, 2021, b). Selectivity for S. aureus is important because S. aureus causes atopic dermatitis and skin roughness, whereas S. epidermidis is beneficial because it helps maintain a healthy epidermis and enhances innate immunity (Kobayashi et al, 2015; Naik et al, 2015; Novick, 2003).…”
Section: Introductionmentioning
confidence: 99%